2022
DOI: 10.1007/s40620-022-01257-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe breakthrough SARS-CoV-2 infections in vaccinated kidney transplant and haemodialysis patients

Abstract: Introduction Given the increased COVID-19 observed in kidney transplant recipients (KTRs) and haemodialysis patients, several studies have tried to establish the efficacy of mRNA vaccines in these populations by evaluating their humoral and cellular responses. However, there is currently no information on clinical protection (deaths and hospitalizations), a gap that this study aims to fill. Methods Observational prospective study involving 1,336 KTRs and haemodialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Serological findings of this cohort were comparable with those described by other groups that studied serology up to 32 weeks after receiving the BNT162b2 vaccine [44][45][46][47][48][49][50][51][52]. Of note, many of these studies monitored vaccine-induced antibody responses in either patients with multiple pathologies (e.g., multiple sclerosis, hemodialysis) [44][45][46]53,54], SARS-CoV-2 convalescent patients [55][56][57] or between patients receiving one, two or three doses of the BNT162b2 vaccine [57,58]. These different set-ups complicate an accurate comparison between datasets.…”
Section: Discussionsupporting
confidence: 84%
“…Serological findings of this cohort were comparable with those described by other groups that studied serology up to 32 weeks after receiving the BNT162b2 vaccine [44][45][46][47][48][49][50][51][52]. Of note, many of these studies monitored vaccine-induced antibody responses in either patients with multiple pathologies (e.g., multiple sclerosis, hemodialysis) [44][45][46]53,54], SARS-CoV-2 convalescent patients [55][56][57] or between patients receiving one, two or three doses of the BNT162b2 vaccine [57,58]. These different set-ups complicate an accurate comparison between datasets.…”
Section: Discussionsupporting
confidence: 84%
“…Our results support the idea that it might be more appropriate to consider broader antibody ranges than to establish a single cutoff point. Indeed, according with other publications, 3,23,24 our results support that other factors such as a history of diabetes were associated with an increased risk of death, but early minimization of MPA was associated with a lower risk of mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Patients without detectable anti-RBD antibody levels were included in our study, reflecting individuals at exceptionally high risk for severe COVID-19 disease courses. Although none of the patients seroconverted after primary vaccination, the heterogeneity of the patient cohort has to be considered since it has been reported that underlying disease-specific medication can contribute to vaccination response [34][35][36] . While antibody levels have been determined at multiple time points during clinical routine before booster vaccination, it cannot be ruled out that individual patients had developed transient antibodies prior to study inclusion.…”
Section: Discussionmentioning
confidence: 99%